Formulation And Evaluation Of Mouth Dissolving Tablet Of Amlodipine - Ojha, Priyanshu Krishna; Pandey, Jai Deo (Journal of Neonatal Surgery, 2025)
The present study focuses on the Formulation and evaluation of mouth-dissolving tablet (MDTs) of Amlodipine, a widely used antihypertensive drug with poor bioavailability due to first-pass metabolism. Mouth-dissolving tablets offer a promising alternative to conventional tablets, particularly for patients with dysphagia, by enhancing convenience, compliance, and rapid drug absorption through pre-gastric absorption. The MDTs were prepared using Direct-Compression and using various Super-disintegrants to ensure rapid disintegration and dissolution. The formulations were optimized based on pre-compression parameters (angle of repose, bulk density, compressibility index) and post-compression parameters (weight variation, hardness, friability, wetting time, disintegration time, drug content and in vitro dissolution). The optimized formulation exhibited rapid disintegration (within 30 seconds) and high drug release (>90% within 15 minutes), meeting Pharmacopeial standards. Stability studies coAFirmed the formulation's robustness under varying conditions. In vitro drug release kinetics followed the Korsmeyer-Peppas model, indicating diffusion-controlled release. This study demonstrates the successful development of Amlodipine MDTs with improved patient compliance, faster onset of action, and enhanced bioavailability, making them a viable alternative to conventional dosage forms